Engineering Transformations of the New York State Canal System and Long-Term Environmental and Public Health Implications - Kenneth R. Olson (Pollution and Diseases, 2026)
Three major rivers—the Hudson, Mohawk, and Passaic—together with the New York State Canal System form an interconnected set of waterways that helped shape settlement, transportation, industry, and urban growth in the northeastern United States. Over the past two centuries, canals, channels, locks, dams, floodwalls, reservoirs, and repeated dredging transformed natural drainage systems and connected water bodies that had previously been separated. This review examines three linked case studies: the Hudson River and its legacy of polychlorinated biphenyl (PCB) contamination; the New York State Canal System and its economic, ecological, and public-health consequences; and the Passaic River, where Agent Orange manufacture contributed to long-term dioxin TCDD contamination of river sediments. The canal system accelerated commerce and migration but also created pathways for waterborne disease and invasive species, including the nineteenth-century spread of cholera and the movement of sea lamprey into inland waters. Industrialization along the Hudson produced persistent PCB contamination that required extensive dredging, monitoring, and Superfund remediation. Along the lower Passaic River, dioxin TCDD, PCBs, and mercury remain associated with contaminated sediments, fish and crab consumption restrictions, and multi-billion-dollar cleanup and natural-resource restoration efforts. Taken together, these cases show that hydrological engineering can create major social and economic benefits while also redistributing pollutants, biological agents, and ecological risks across connected water systems. Long-term management therefore requires integrated attention to hydrology, sediment, ecology, public health, monitoring, remediation, and governance.